Molecular mechanisms of an antimicrobial peptide piscidin (Lc-pis) in a parasitic protozoan, Cryptocaryon irritans - Ruanni Chen (BMC Genomics, 2018)
Abstract Background Cryptocaryon irritans is an obligate parasitic ciliate protozoan that can infect various commercially important mariculture fish species and cause high lethality and economic loss. Current methods of controlling this parasite with chemicals or antibiotics are widely considered to be environmentally harmful. Piscidins with broad spectrum antibacterial, antifungal and antiviral activities were found to have potent activity against C. irritans. Little, however, has been understood about the killing mechanisms of piscidins in parasites. Results In total, 57.12, 50.44, 55.86 and 47.87 million raw reads were generated from untreated theront and trophont, and piscidin (Lc-pis) treated theront and trophont libraries, respectively. After de novo assembly, 966,609 unigenes were generated with an average length of 420 bp: among these, 618,629 unigenes showed identity with sequences in one or more databases, with some showing to be significantly manipulated by Lc-pis treatment. The species classification showed that more than 25.8% unigenes from trophonts were homologous to the large yellow croaker (Larimichthys crocea) and less than 3.8% unigenes from theronts were matched. The homologous unigenes demonstrated that the tissue from host could exist in trophonts and might be transported to parasite via vesicular transports. Our analysis showed that regulatory transcripts were involved in vesicular trafficking. Among transcripts induced by Lc-pis, most genes up-regulated in treated and untreated theronts were involved in cell migration and apoptosis related pathways. Few transcripts were found to be down-regulated in treated and untreated trophonts related to cell structure and migration after treatment. Conclusions This is the first transcriptome analysis of C. irritans exposed to Lc-pis, which enhanced the genomic resources and provided novel insights into molecular mechanisms of ciliates treated by cationic antimicrobial peptide. Our comprehensive transcriptome analysis can facilitate the identification of potential drug targets and vaccines candidates for controlling this devastating fish pathogen.